Association of financial assistance programs and time to completion of therapy in women receiving chemoradiation for cervical cancer - Jessica M. Gillen; Sarah C. Grimes; Kathleen G. Essel; Grace E. Duininck; Daniel Zhao; John S. Thompson; Debra L. Richardson (Elsevier, 2020)
We aimed to evaluate how the need for social services programs is associated with outcomes amongst patients with cervical cancer undergoing chemoradiation with a single institution, retrospective analysis of patients from January 1, 2015-July 31, 2018. Demographic, clinical, and social services utilization data were collected. Descriptive statistics and Chi-squared tests were performed. Kaplan-Meier curves estimated progression free (PFS) and overall survival (OS).Among 117 eligible patients, median household income was $45,782 ($19,771 - $96,222). There was no difference in stage among income cohorts. Uninsured/publically insured patients had a higher stage at diagnosis than those privately insured (p = 0.003). Patients used 0-5 assistance programs during treatment. 77.6% of low income versus 54.2% of high income patients utilized ≥1 program. Assistance with lodging was utilized more often in low than high income patients.(36.2% vs 15.7%, p = 0.013). 58.3% of patients completed therapy in less than 56 days. Patients who completed therapy in >56 days utilized 1.44 social services while patients completing in ≤56 days used 1.06 (p = 0.102). Social security disability utilization trended towards completion times >56 days (p = 0.064). There was no difference in PFS or OS based on income or social services utilized.Financial toxicities associated with therapy are not limited to uninsured/publically insured or low income patients as over 50% of high income patients utilized at least one service. Additionally, the trend towards significance between enrollment in disability and completion of chemoradiation >56 days may highlight a group of at risk patients who need additional support.